El fideicomiso mercantil de garantía y los derechos constitucionales del deudor - Martín Vanegas, Andrés Valentino (2016)
The Guaranty Trust is still in constant development in Latin America and our Country. This investigation is a source of knowledge for its readers and audience, being able to enrich their knowledge regarding this legal institution, allowing them to understand it and assess the impact it produces on the constitutional rights of the debtor in Ecuador. The cognitive elements include a logic and historic development of the Trust, from its origin in Rome until nowadays. The key instrument of this investigation goes through a complete review of the Guaranty Trust, including a legal and constitutional exam of the institution regarding the restrictive amend promulgated on de Bill for Optimization and Strengthening of the corporate and securities industries on year 2014……..